Application of Probiotics for Organic Matter and Enhancement of Growth Performance in White Shrimp (Litopenaeus vannamei) - Muhammed Jefri; Woro Hastuti Satyantini; Adriana Monica Sahidu; Daruti Dinda Nindarwi; Rozi Rozi (Jurnal Ilmiah Perikanan dan Kelautan, 2020)
HighlightsLitopenaeus vannamei has been established as alternative to Penaeus monodon to shrimp farming in several countries.Increased importance of in situ microorganisms both in regulating biogeochemical cycles within the culture environment and in directly affecting shrimp growth and survival.To improve water quality in aquaculture is the application of probiotics and/or enzymes to ponds. AbstractIntensive shrimp farming has raised environmental issues due to aquaculture pollution, which is caused by uneaten feed, feces, organic matter, and toxic compounds (ammonia and H2S). One way to solve this issue is by using probiotics. Thus, this study aimed at investigating the effect of probiotic administration (Pseudomonas sp. and Bacillus sp.) at varying concentrations on total organic matter in the rearing water, feed conversion ratio, feed efficiency, and growth rate of white shrimp (Litopenaeus vannamei). This study used a Completely Randomized Design consisting of four treatments: T0 (without the probiotic supplementations), T1 (probiotics at 106 CFU/ml), T2 (probiotics at 107 CFU/mL), T3 (probiotics at 108 CFU/mL) with three replicates each. The results showed that the administration of probiotics at different concentrations had a significant effect on the total amount of organic matter, feed conversion ratio, feed efficiency, and specific growth rate of white shrimp. Administration of probiotics at a concentration of 107 CFU/ ml had the lowest organic matter in the rearing water, 138 mg /Lt. While probiotic administration at 108 CFU/ ml gave the lowest feed conversion ratio (1.22), the highest feed efficiency (81.57%) and the best growth rate (2.25%/day). This research suggests that the administration of 107-108 CFU/ ml probiotics could be applied to reduce organic content in the rearing water and improve the growth performances of white shrimp.